(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2025)
The main objective of this research article is to perform a comparative analysis by varying the three characteristics evaluated, which correspond to population, biological oxygen demand (BOD) and temperature. This research consisted of determining the characteristics of the six facultative stabilization ponds to achieve a decrease in the BOD present. The limitations of the lagoons were determined by means of tables and graphs that represent the aforementioned information, taking into account the ranges established by the authors. The results showed that the temperature values are of great importance at the time of calculating the variables used since they have influence and are directly related to them, as well as the presence of high and low populations with the presence of high and low BOD ranges.